Numerical Solution of Time Fractional Parabolic Differential Equations - R.Ramesh Rao, T. (International Journal of Engineering and Technology, 2018)
In this paper, we study the coupling of an approximate analytical technique called reduced differential transform (RDT) with fractional complex transform. The present method reduces the time fractional differential equations in to integer order differential equations. The fractional derivatives are defined in Jumaries modified Riemann-Liouville sense. Result shows that the present technique is effective and powerful for handling the fractional order differential equations.Â